The Effect Of Organizational Learning Culture, Technology Readiness And Institutional Support On Educational Organizational Resilience In Higher Education Institutions - Firman Aziz; Novelti; Ahmad Nur Budi Utama; Zuhair Mubarrak Hazaa; Wahyu Inggar Fipiana; Saparuddin Rambe (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The objective of this research is to find out how the Organizational Learning Culture, Technology Readiness, and Late Support can affect the Organizational Resilience in Indonesia’s higher education institutions. Quantitative research will be conducted through surveys, with question responses collected from 190 respondents consisting of lecturers and other educational personnel using purposive sampling (only those picked as part of this group). Criteria for inclusion in this sample are as follows, all included must have been employed in their current position for at least two years, work in both Academic and Administrative areas and have some experience using Digitial systems at work Therefore the chosen method to analyse this data will be by employing Multiple Linear Regression techniques. The data analysis will be tempered by conducting preliminary testing upon completion including Validity and Reliability tests, as well as tests for Normality, Heteroscedasticity and Multicollinearity assumptions. The research produced evidence that showed a significant, positive relationship between Organizational Learning Culture, Technology Readiness, and Institutional Support with respect to Organizational Resilience. Therefore, one could say that enhancing the resilient nature of an organisation is dependent upon enhancing an organization’s learning culture, increasing technology readiness, and enhancing Institutional Support. This research seeks to support the creation of sustainable management models for higher education institutions that are more adaptable in the present and future.